1996
DOI: 10.1111/j.1432-1033.1996.0132r.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the 1H‐NMR Chemical Shifts of Cu(I)‐, Cu(II)‐ and Cd‐Substituted Pea Plastocyanin

Abstract: To compare cadmium-substituted plastocyanin with copper plastocyanin, the 'H-NMR spectra of CuI-, Curl-and Cd-plastocyanin from pea have been analyzed. Full assignments of the spectra of CuIand Cd-plastocyanin indicate chemical shift differences up to 1 ppm. The affected protons are located in the four loops that surround the Cu site. The largest differences were found for protons in the hydrogen bond network which stabilizes this part of the protein. This suggests that the chemical shift differences are cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 68 publications
3
49
0
Order By: Relevance
“…To elucidate the PSI binding mode of Pc in more detail, the Pc-PSI interaction was further investigated under conditions where the interactions on the hydrophobic patch of Pc were perturbed by cadmium substitution. A comparison of the 1 H-15 N shift correlation spectra of uniformly [ 15 N]-labeled Pc and cadmium-substituted Pc (Cd-Pc) revealed that the signals that exhibited significantly different chemical shifts were all those from the hydrophobic patch residues, consistent with the previous report for Pcs from different species (Ubbink et al, 1996), suggesting that the Cd-Pc is correctly folded (see Supplemental Figures 6A and 6B online). Although the distance between the amide proton of Gly-8 and the Hb of Phe-14, which are located at the stem of the loop1, is 9.5 Å in the structure of reduced Pc, a nuclear Overhauser effect, which is usually observed for hydrogen atom pairs with <5 Å distance, was observed between the corresponding hydrogen atoms in CdPc, suggesting that the conformation of loop1 in the hydrophobic patch is perturbed by the cadmium substitution.…”
Section: Effect Of Perturbation Of the Interactions On The Hydrophobisupporting
confidence: 65%
See 2 more Smart Citations
“…To elucidate the PSI binding mode of Pc in more detail, the Pc-PSI interaction was further investigated under conditions where the interactions on the hydrophobic patch of Pc were perturbed by cadmium substitution. A comparison of the 1 H-15 N shift correlation spectra of uniformly [ 15 N]-labeled Pc and cadmium-substituted Pc (Cd-Pc) revealed that the signals that exhibited significantly different chemical shifts were all those from the hydrophobic patch residues, consistent with the previous report for Pcs from different species (Ubbink et al, 1996), suggesting that the Cd-Pc is correctly folded (see Supplemental Figures 6A and 6B online). Although the distance between the amide proton of Gly-8 and the Hb of Phe-14, which are located at the stem of the loop1, is 9.5 Å in the structure of reduced Pc, a nuclear Overhauser effect, which is usually observed for hydrogen atom pairs with <5 Å distance, was observed between the corresponding hydrogen atoms in CdPc, suggesting that the conformation of loop1 in the hydrophobic patch is perturbed by the cadmium substitution.…”
Section: Effect Of Perturbation Of the Interactions On The Hydrophobisupporting
confidence: 65%
“…The substitution of the copper ion of Pc with a cadmium ion reportedly shifts the hydrogen bond network in the hydrophobic patch to a configuration resembling that in the oxidized Pc, without affecting the conformations of the other regions, including the acidic patch (Ubbink et al, 1996). To elucidate the PSI binding mode of Pc in more detail, the Pc-PSI interaction was further investigated under conditions where the interactions on the hydrophobic patch of Pc were perturbed by cadmium substitution.…”
Section: Effect Of Perturbation Of the Interactions On The Hydrophobimentioning
confidence: 99%
See 1 more Smart Citation
“…7 shows that 1 H and 15 N chemical shift differences are found in the regions encompassing all four northern loops, whereas none of the regions around the southern loops are involved. Whereas 15 N chemical shift differences have been discussed in terms of very minor steric/ electronic variations (69 -75), the 1 H chemical shift differences can be tentatively ascribed to modest structural modifications consequent to a redox state change of the copper ion, as also found in a similar analysis for pea plastocyanin (72).…”
Section: Discussionmentioning
confidence: 60%
“…In particular, the amide protons located in the four loop regions surrounding the metal site undergo significant changes in chemical shift, as was also observed previously in the case of pea plastocyanin. 31 These changes clearly demonstrate the importance of choosing a proper diamagnetic reference. …”
Section: Choosing a Diamagnetic Referencementioning
confidence: 99%